Procedimiento para la formulación de constructos en mercadeo - Stella Isabel Domínguez Sandoval (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– A critical element in the evolution of a fundamental body of knowledge in marketing, as well as for improved marketing practice, is the development of measures of the variables with which marketers work. Colombian companies are using adapted tools from original English language found freely on Internet or marketing texts books. Because measure constructs more complex phenomena, this practice decreases the effectiveness in managing the marketing for the reliability and validity of the translated instrument is not measured. From the results obtained in this research, the need to explain a general process for developing constructs in terms that meet the needs of appropriate instruments and as a basis for future studies is evident.
Keywords: M31; C38; 330; marketing management; marketing constructs; multi-items scales; Cronbach's alpha coeficient; construct validity